Hyperbolic Phonon Polaritons: Broad‐Spectral‐Range Sustainability and Controllable Excitation of Hyperbolic Phonon Polaritons in α‐MoO3 (Adv. Mater. 46/2020). Issue 46 (17th November 2020) - Dong, Weikang; Qi, Ruishi; Liu, Tiansheng; Li, Yi; Li, Ning; Hua, Ze; Gao, Zirui; Zhang, Shuyuan; Liu, Kaihui; Guo, Jiandong; Gao, Peng
Abstract : In article number 2002014, Peng Gao and co‐workers use an electron probe to selectively excite hyperbolic phonon polaritons in multiple frequency bands covering both the mid‐ and far‐infrared in α‐MoO3 . The broad‐spectral‐range sustainability together with highly anisotropic excitation and propagation behavior of these polaritons may find potential applications in nanoscale confinement and manipulation of light.